The oxidative desaturation of unsaturated fatty acids in animals - Brenner, Rodolfo Roberto (1974)
The progress made in the knowledge of the microsomal fatty acid desaturation reaction is described: 1) Studies suggest that different enzymes produce 9, 6, and 5-desaturation. 2) The 6-desaturation of fatty acids would be the principal regulatory step in the biosynthesis of polyunsaturated fatty acids in rat microsomes. 3) The desaturation of fatty acids is quantitatively modified by competitive reactions among acids of the same or different families, and by competition with fatty acid incorporation in the lipids. 4) Dietary components, especially carbohydrates and protein modify quantitatively the fatty acid desaturation. Protein would induce the 6-desaturation reaction. 5) Insulin modifies the 6-desaturation reaction through a dual effect: one modifying glucose metabolism, and the other through enzymatic induction. 6) ATP increases the 6-desaturation of fatty acids 7) By mild extraction of the microsomes with buffered KCl sucrose solution, a “soluble” fraction was separated that was necessary for a full desaturation activity of the microsomes. The nature of this factor is discussed. 8) The main features that characterize the 6-desaturation reaction are discussed and the possible structure of the enzyme outlined.